Utilization of catalyzed waste vegetable oil as a binder for the production of environmentally friendly roofing tiles. (1st March 2017) - Nadeem, Humayun; Habib, Noor Zainab; Ng, Choon Aun; Zoorob, Salah Elias; Mustaffa, Zahiraniza; Chee, Swee Yong; Younas, Muhammad
Abstract: Climate change has become a major issue in recent years owing to the emission of greenhouse gases. Mitigation measures are required to overcome the challenges pertained to greenhouse gases emissions. This research paper attributes to the utilization of catalyzed waste vegetable oil as a binder for the production of roofing tiles to replace the conventional construction materials such as clay and cement. A novel methodology of utilizing catalyzed waste oil incorporated with sand and filler was adopted and the innovative product produced is entitled as catalyzed Vege-Roofing tiles that discovered to be economical and environmentally friendly in contrast to the traditional binders. It is believed that an extended heat curing of vegetable oil resulted in a complex oxy-polymerization reaction converting it into a rigid binder. Triplicate prototypes samples were manufactured to optimize the final conditions for the fabrication of catalyzed Vege-Roofing tiles. Optimized conditions were then implemented to produce standard catalyzed Vege-Roofing tiles and these fabricated tiles have shown flexural stress of up to 12 MPa for 18 h of curing. Moreover, these novel tiles were tested for permeability and water absorption according to the ASTM standards and have shown impermeability and remarkably low water absorption. Progressively, the embodied energy and embodied carbon requirements for these tiles found to be 0.64 MJ/kg and 0.327 kg CO2 per equivalent respectively which is quite less in comparison to the traditional binders. Conclusively, environmentally friendly and economic production of tiles, conservation of existing resources and overcoming the issue of waste management are the remarkable outcomes of this research. Graphical abstract: Highlights: Substituting the traditional binders for building industry. To produce environmentally friendly and economical roofing tiles. Utilisation of industrial symbiosis to fabricate novel tiles.